Remoção de sulfato em efluentes de curtume usando processo biológico - Lima, Eveline Cunha (2010)
The research aimed to analyze the stability and efficiency of the anaerobic sulfate reduction applied to the treatment of effluent from a tannery. It was used two anaerobic reactors upflow anaerobic sludge blanket (UASB), with capacity of 3.0 liters, constant temperature of 29 + 2°C and hydraulic detention times of 12 and 24 hours. The reactors were operated with synthetic influent and then with real influent. First, synthetic influent was studied using DQO/SO4 -2 ratio of 1.4, 0.8 and 0.5. The results showed that DQO/SO4 -2 ratio of 0.8 showed the best removal efficiency of COD (87,8%) and removal of sulfate (38,7%). After, the reactor was fed with real influent and removals of COD ranged from 20.4 to 58.5% and removal of sulfate from 39.4 to 73.9% in the different phases of this study. The sulfide formed inside the reactor helped remove chromium present in the real influent from 39.7 to 77.6%. In all experiments the reactor was stable in the production of alkalinity and total volatile fatty acid concentration was maintained at adequate levels. The results showed that the use of the process of sulfate reduction in UASB reactors is presented as a promising alternative to pretreat effluents from tannery, to meet the release limits imposed by environmental agencies.